Pengembangan Lembar Kerja Investigasi Terintegrasi Web pada Materi Protista - Lely Mardiyanti (Postgraduate, University of Mataram, 2024)
This study aims to produce a web-integrated investigation worksheet about protists that is valid, practical, and effective by following the McKenney & Reeves development model. The validity of the worksheet was obtained by filling out a validation questionnaire by teaching material experts and microbiology experts. The practicality of the worksheet was obtained through filling out response questionnaires by students and biology teachers. Meanwhile, the effectiveness of the worksheet was obtained from the difference in students' pretest and post-test scores. The results of filling out the validation questionnaire and response questionnaire were analyzed using percentages while the difference in student test scores was analyzed using paired t-test. The average of expert validation results obtained a value of 88.6% (valid). Implementation on 30 students of class X IPA SMA Islam Kepanjen Malang using the group investigation learning model showed that the worksheet proved to be very practical based on the average response which amounted to 89.3%. In addition, the paired t-test results showed that there was a big difference between the students' test scores before (M = 37.500, SD = 13.310) and after using the worksheet (M = 77.033, SD = 13.013), t(29) = 18.203, p <0.001, d = 3.323. So, it can be concluded that the web-integrated investigation worksheet about protists is considered valid, very practical, and effective.